Doubling mental rotation scores in high school students: Effects of motivational and strategic trainings. (August 2021) - Moè, Angelica
Abstract: Achievement in mathematics, science, biology, chemistry, and other school subjects requiring abstract reasoning on spatial relationships is favored by mental rotation abilities, that is by the capability to mentally manipulate objects in space. This suggests the need to develop effective trainings aimed at improving mental rotation performance. Previous research focused mostly on practice with spatial tasks. Since motivational beliefs, gender stereotypes and self-confidence can affect performance, this research tested the hypothesis that a training including motivational aspects will be effective as well. Two intervention studies with high school students ( n  = 122 and n  = 70 respectively) confirmed that a three-session-training based on allowing practice in adopting a holistic strategy to solve the mental rotation items or on fostering effective motivational beliefs increased the mental rotation scores up to 1 SD. The discussion focuses on the characteristics of effective trainings aimed at improving mental rotation abilities in high school students. Highlights: Mental rotation abilities can be improved in high school students. A 3-sessions training teaching adoption of a holistic strategy was effective. A training focused on motivational beliefs and self-competence was equally effective. The effects could be observed after the second training session.